REACH of Interventions Integrating Primary Care and Behavioral Health - Balasubramanian, Bijal A. (J Am Board Fam Med, 2015)
PURPOSE: This study reports REACH (the extent to which an intervention or program was delivered to the identified target population) of interventions integrating primary care and behavioral health implemented by real-world practices. METHODS: Eleven practices implementing integrated care interventions provided data to calculate REACH as follows: 1) Screening REACH defined as proportion of target patients assessed for integrated care, and 2) Integrated care services REACH—defined as proportion of patients receiving integrated services of those who met specific criteria. Difference in mean REACH between practices was evaluated using t test. RESULTS: Overall, 26.2% of target patients (n = 24,906) were assessed for integrated care and 41% (n = 836) of eligible patients received integration services. Practices that implemented systematic protocols to identify patients needing integrated care had a significantly higher screening REACH (mean, 70%; 95% CI [confidence interval], 46.6–93.4%) compared with practices that used clinicians’ discretion (mean, 7.9%; 95% CI, 0.6–15.1; P = .0014). Integrated care services REACH was higher among practices that used clinicians’ discretion compared with those that assessed patients systematically (mean, 95.8 vs 53.8%; P = .03). CONCLUSION: REACH of integrated care interventions differed by practices’ method of assessing patients. Measuring REACH is important to evaluate the extent to which integration efforts affect patient care and can help demonstrate the impact of integrated care to payers and policy makers.